Development and Preliminary Validation of the Lovebird Scale - Sara Cloonan; Lara Ault; Karen L. Weihs; Richard D. Lane (Behavioral Sciences)
The term “lovebirds” is often used to describe the loving behaviors and interactions between two romantic partners, but what specific processes distinguish these flourishing lovebird relationships from other committed but “numbed” relationships? The present study aimed to address this knowledge gap through the development and preliminary validation of the Lovebird Scale. The Lovebird Scale describes the thoughts, feelings, behaviors, and habits that constitute and maintain relationship flourishing, which in turn could promote aspects of individual flourishing such as positive affect. We conducted three studies using data collected from 996 English-speaking U.S. adults (64.2% Female, M = 39.2 years old) who reported being in a romantic relationship for at least six months (M = 11.2 years). In Study 1, we conducted an exploratory factor analysis to determine the underlying factor structure. In Study 2, confirmatory factor analyses revealed a three-factor model nested within a higher-order factor representing lovebird relationships. In Study 3, we cross-validated the higher-order structure, examined the construct validity of the scale, and explored associations between the Lovebird Scale and affective state. Finally, we discuss how the Lovebird Scale contributes to the growing field of positive relationship science as well as conceptual and clinical implications of the scale.